Need Analysis to Develop E-Student Worksheet Integrated PBL Model and Virtual Laboratory to Improve Students' Problem-Solving Skills - Husnul Chotima; Selma Riyasni; Asrizal Asrizal; Dea Stivani Suherman (Journal of Innovative Physics Teaching, 2026)
Problem-solving skills are essential competencies in 21st-century physics learning. A preliminary observation at SMAN 8 Padang revealed that all indicators of students' problem-solving ability on the Static Fluid material were in the low category, with an overall average of 30.52%. Instructional materials were dominated by textbooks, teaching was teacher-centered, and laboratory activities were rarely conducted due to limited equipment. This study aimed to analyze the needs for developing an Electronic Student Worksheet integrated with the Problem Based Learning model and a virtual laboratory on the Static Fluid topic. Data were collected through teacher interviews, questionnaires, infrastructure observation, and curriculum document analysis. Results showed that teachers lacked a Problem Based Learning-based digital worksheet, students were strongly interested in interactive digital media (average need score 75.00% for the Electronic Student Worksheet and 76.47% for the Problem Based Learning model), the school possessed adequate digital infrastructure, and the Static Fluid topic was highly suitable for Problem Based Learning implementation. These findings provide an evidence-based foundation for developing a Problem Based Learning-integrated Electronic Student Worksheet assisted by a virtual laboratory to improve students' problem-solving skills.